Determination of Glutamine and Arginine in Human Serum by Capillary Electrophoresis with UV Detection - Shanshan, Jia; Bin, Luo; Ying, Zhao; Zengning, Li; Weijun, Kang (Asian Journal of Chemistry, 2011)
A rapid method for the determination of glutamine and arginine in serum is presented. Derivatization of glutamine and arginine using phenyl isothiocyanate were separated and detected in 8 min by high performance capillary electrophoresis with UV detection on 254 nm. The separation and determination condition were as follows: gravitation sampling, the time is 15 s, the height is 25 cm; running voltage 15 kv; bouncy silica capillary: 75 μm i.d., total length 70 cm, 58 cm from the inlet to UV detection; electrolyte, 20 mmol/L sodium tetraborate, 166 mmol/L lauryl sodium sulfate and acetonitrile, pH 9.33. The linear ranges of glutamine is 0.03- 1.90 mmol/L and arginine is 0.03-1.50 mmol/L, r is 0.996-0.998. This new method could be used to determine the glutamine and arginine in human serum. The result was proved to be satisfactory.